2012
DOI: 10.1089/dna.2011.1565
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of DNA Methylation in Aging and Alzheimer's Disease

Abstract: Gene expression is modulated by epigenetic factors that come in varying forms, such as DNA methylation, histone modifications, microRNAs, and long noncoding RNAs. Recent studies reveal that these epigenetic marks are important regulatory factors in brain function. In particular, DNA methylation dynamics are found to be essential components of epigenetic regulation in the mammalian central nervous system. In this review, we provide an overview of the literature on DNA methylation in neurodegenerative diseases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 93 publications
2
63
0
2
Order By: Relevance
“…Recent studies have shown that DNA methylation has roles in both disease and normal neuronal function. Once considered to be a stable epigenetic mark that was primarily altered in development and cancer, DNA methylation has now been linked to a wide variety of diseases, including insulin resistance, cardiovascular disease, and neurological disorders (54)(55)(56). In fact, even normal neuronal activity causes rapid changes to DNA methylation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that DNA methylation has roles in both disease and normal neuronal function. Once considered to be a stable epigenetic mark that was primarily altered in development and cancer, DNA methylation has now been linked to a wide variety of diseases, including insulin resistance, cardiovascular disease, and neurological disorders (54)(55)(56). In fact, even normal neuronal activity causes rapid changes to DNA methylation.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this data, it is thought that the patterns of cytosine modifications acquired throughout neuronal development are critical for proper neurodevelopment and neurological function in the adult brain. In fact, recent studies have implicated epigenetic regulation in both Alzheimer's and Huntington's diseases [7,44,64]. Together, these observations strongly suggest that 5hmC plays a critical role in brain development and related diseases [43].…”
Section: -Hydroxymethylcytosinementioning
confidence: 94%
“…As previously mentioned, the recently discovered TET family of dioxygenases is believed to mediate the oxidation of 5mC thereby priming it for removal by the Base Excision Repair pathways (BER) [92]. Disruption of the epigenetic machinery responsible for active demethylation can lead to age-specific 5hmC profiles [138] and/or DNA demethylation profiles [139]. Interestingly, methylation drift is associated with promoter hypomethylation of PSEN1 and APOEgenes important in the age-dependant onset of neurodegenerative diseases such as AD [139].…”
Section: Mechanism Of Age-related Methylation Driftmentioning
confidence: 99%